Effect of storage conditions on the bromelain activity of pineapple peel variety Josapine / Muhammad Yazid Abd Halim, Siti Aimi Sarah Zainal Abidin and Siti Roha Ab Mutalib - Abd Halim, Muhammad Yazid; Zainal Abidin, Siti Aimi Sarah; Ab Mutalib, Siti Roha (Faculty of Applied Sciences, 2024)
Bromelain is a complex mixture of proteolytic enzymes typically derived from pineapple peels, leaves, stems, and fruit. This study aimed to determine the effect of storage conditions on the bromelain activity of the pineapple peel variety Josapine. The production of bromelain powder in this study was done in four steps: the extraction of crude bromelain from pineapple peel extracts, the purification of bromelain using ammonium sulfate precipitation, desalting using the diafiltration process, and finally, freeze drying using a freeze dryer. The casein digestion unit (CDU) analytical method determined the protease activity. The bromelain powder obtained from the pineapple peel extract was stored at three different temperatures: -20 °C, 4°C, and 27°C. Results showed that bromelain powder stored at a freezing temperature had the lowest decrement of bromelain activity when stored for up to one month. Bromelain powder stored at 27°C lost almost 90% of its activity upon one month of storage time. A freezing temperature below -20 °C was the best condition to sustain the enzymatic activity of bromelain.